2018
DOI: 10.11648/j.jgo.20180601.11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Thiol/Disulphide Homeostasis in Patients with Vaginitis

Abstract: This study investigated the thiol-disulphide balance in vaginitis, which is a local inflammatory condition, through the use of a new method. A cross-sectional study involving 82 women (45 women with vaginitis and 37 women in control group) was conducted at Ataturk Education and Research Hospital, Ankara, Turkey from February 2016 to April 2016. Their ages varied between 19-75 years (mean: 42.8±11.6), were incorporated into the study. Thiol-disulphide parameters were measured and the obtained results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that TDH was shifted in favor of oxidative status in preeclampsia, pregnant women diagnosed with idiopathic recurrent pregnancy loss, pregnant women diagnosed with Familial Mediterranean fever, pregnant women with fetal neural tube defects and vaginitis patients [89][90][91][92][93].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%
“…It has been demonstrated that TDH was shifted in favor of oxidative status in preeclampsia, pregnant women diagnosed with idiopathic recurrent pregnancy loss, pregnant women diagnosed with Familial Mediterranean fever, pregnant women with fetal neural tube defects and vaginitis patients [89][90][91][92][93].…”
Section: Obstetric and Gynecologic Disordersmentioning
confidence: 99%